TRADEMARK AND LOGO REGISTRATION MECHANISM ON BEHALF OF DE’ FLORIST - Eny Eny; Agustianto Agustianto (Universitas Internasional Batam, 2022)
The development of technology that cannot be avoided by the community and its rapid distribution flow, of course, can provide benefits for business actors in developing their business. Branding on products that are marketed becomes a marker for the community. This study aims to test empirically related to the implementation through a trademark registration mechanism. The method used in this activity is qualitative by developing the theory and implementing it, which is then compiled in a report on community service activities. The results of these activities such as understanding more about a brand, the function of the mark, the mechanism for registering a mark which is carried out online, and the benefits received after registering a mark for online business actors.